Trends in breast cancer mortality in Peru and its geographical areas from 2013 to 2022 and prediction until 2027 - Terrel Poccomo, Melanie Kiara (2025)
Background: In 2022, breast cancer was one of the most commonly diagnosed neoplasms and the leading cause of cancer death among women worldwide. In Peru, reports on mortality due to this neoplasm are scarce, especially after implementing strategies to reduce its impact. This study aimed to estimate mortality rates for breast cancer in Peru and its geographic regions from 2013 to 2022 and to project its evolution to 2027. Methods: An observational ecological study of multiple time series was conducted. Data were obtained from the Ministry of Health’s death database via SINADEF. Mortality rates per 100,000 women were calculated using the direct method and Segi’s world standard population. Mortality trends were analyzed using the Annual Percent Change (APC) calculated with Joinpoint regression software. Predictions for 2027 were also made using the Nordpred package in R Studio. Results: In 2013, the departments with the highest breast cancer mortality rates in Peru were Ica, Callao, Lambayeque and La Libertad. In 2022, Ancash and Tumbes were added, with Tumbes having the highest rates. For women under 50, Lambayeque and Madre de Dios led in 2013, while for women over 50, Tumbes had the highest mortality rate in 2022. Peru reported a significant increase of 3.97% on an annual basis for the entire period. According to regions, Rainforest region (APC = + 8.37) and the Rainforest region (APC = + 11.55) showed significant increases in mortality rates, while no significant changes were observed in the Coastal region. Moreover, an increase in breast cancer mortality in Peru is projected for the year 2027. Conclusion: Breast cancer mortality in Peru has shown a constant increase, with significant regional disparities. The highest rates were recorded in the coastal region, although the Andean and jungle regions experienced the most pronounced increases. These disparities may be attributed to data underreporting during the COVID-19 pandemic and unequal access to diagnostic and treatment services. The findings highlight the urgent need for focused public health interventions to reduce these regional gaps and improve breast cancer management outcomes. © The Author(s) 2025.